Research on dynamic compression failure characteristics and damage constitutive model of sandstone after freeze–thaw cycles. (October 2022) - Zhai, Yue; Meng, Fandong; Li, Yubai; Li, Yan; Zhao, Ruifeng; Zhang, Yunsheng
Highlights: The pore properties of FT sandstone are discussed. The fractal characteristics and energy evolution process of FT sandstone under impact compression are analyzed. A damage constitutive model considering various forms of energy dissipation is established. Abstract: Tongchuan sandstone in northwest China was taken as the research object to study the micro-damage, macro-fracture characteristics and dynamic properties of rocks after freeze–thaw (FT). It is found that almost all of the pores that increased after FT of the sandstone specimens are minipores through the nuclear magnetic resonance test, while the initial pores do not expand further. The Φ50mm split Hopkinson pressure bars (SHPB) equipment was used to test the dynamic compressive properties of sandstone specimens with different FT cycles under different impact speeds, the fractal characteristics, energy evolution and dynamic compressive strength variation laws were discussed. The effect of impact loading on rock is greater than that of FT, and it weakens as the rock softens. A damage constitutive model considering various forms of dissipated energy is proposed, which is closer to the experimental results than the previous damage constitutive model based on energy.